2021
DOI: 10.3390/plants10112459
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Novel and Efficient Agrobacterium-Mediated in Planta Transformation System for Passion Fruit (Passiflora edulis)

Abstract: Passion fruit (Passiflora edulis) is an important fruit crop with high economic value. Genetic engineering plays an important role in crop improvement with desired traits and gene functional studies. The lack of a simple, efficient, and stable transformation system for passion fruit has greatly limited gene functional studies. In this study, a simple and efficient Agrobacterium-mediated in planta transformation system for passion fruit was established, using Agrobacterium virulent strain EHA105 harboring the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Diffused light has positive effect on the shoot regeneration and dark incubation was always found useful in regeneration and transformation experiments. 28 , 29 , 53 , 54 Seedlings took 4–5 weeks for recovery during which, they were regularly irrigated with sterile-double distilled water and Hoagland solution ( Fig. 2g ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Diffused light has positive effect on the shoot regeneration and dark incubation was always found useful in regeneration and transformation experiments. 28 , 29 , 53 , 54 Seedlings took 4–5 weeks for recovery during which, they were regularly irrigated with sterile-double distilled water and Hoagland solution ( Fig. 2g ).…”
Section: Resultsmentioning
confidence: 99%
“… 58 In our experiment, GFP and GUS were used as screenable marker genes and similar studies have been reported in mango, 6 pummelo, 28 and passion fruit. 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potyvirus represents the largest group of plant RNA viruses and comprises a positive-sense single-stranded RNA genome encapsidated by viral coat protein. The potyvirus genome encodes a large polyprotein that is further cleaved into ten mature viral proteins by its own viral proteases (Revers and García, 2015;Cui and Wang, 2019;Dai et al, 2020;Yang et al, 2021). Although potyviruses have been broadly engineered into protein expression vectors, such as tobacco etch virus (TEV), potato virus A (PVA), turnip mosaic virus (TuMV), plum pox virus (PPV), sugarcane mosaic virus (SCMV), wheat streak mosaic virus (WSMV) and zucchini yellow mosaic virus (ZYMV) (Xie et al, 2021), very few potyvirus-based VIGS vector have been reported.…”
Section: Introductionmentioning
confidence: 99%